Harness Organoid Models for Virological Studies in Animals: A Cross-Species Perspective - Sang, Yongming; Miller, Laura C.; Nelli, Rahul K.; Giménez-Lirola, Luis Gabriel (Frontiers in Microbiology, 2021)
Animal models and cell culture in vitro are primarily used in virus and antiviral immune research. Whereas the limitation of these models to recapitulate the viral pathogenesis in humans has been made well aware, it is also imperative to introduce more efficient systems to validate emerging viruses in both domestic and wild animals. Organoids ascribe to representative miniatures of organs (i.e., mini-organs), which are derived from three-dimensional culture of stem cells under respective differential conditions mimicking endogenous organogenetic niches. Organoids have broadened virological studies in the human context, particularly in recent use for COVID19 research. This review examines the status and potential for cross-species applied organotypic culture in validating emerging animal, particularly zoonotic, viruses in domestic and wild animals.